2017
DOI: 10.1055/s-0037-1603809
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography Applied to Patients with Tinnitus: A Review

Abstract: Introduction  Tinnitus has been defined as an “auditory phantom perception,” meaning that tinnitus results from an abnormal activity within the nervous system, in the absence of any internal or external acoustic stimulation. About 10 to 15% of the adult population is affected by tinnitus, and a relevant percentage of tinnitus sufferers experience symptoms severe enough to significantly affect quality of life, including sleep disturbances, work impairment, and, in some cases, psychiatric distress. The self-rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
6
1
2
Order By: Relevance
“…The association of tinnitus with psychopathology is in line with previous cross-sectional studies reporting tinnitus to be associated with depressive and anxiety symptoms and poorer sleep quality . We found that the effect size of the association for bothersome tinnitus over nonbothersome tinnitus was nearly 3 times as large for depressive and anxiety symptoms and twice as large for sleep quality compared with no tinnitus.…”
Section: Discussionsupporting
confidence: 91%
“…The association of tinnitus with psychopathology is in line with previous cross-sectional studies reporting tinnitus to be associated with depressive and anxiety symptoms and poorer sleep quality . We found that the effect size of the association for bothersome tinnitus over nonbothersome tinnitus was nearly 3 times as large for depressive and anxiety symptoms and twice as large for sleep quality compared with no tinnitus.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have also objectively analyzed the sleep of tinnitus patients through polysomnography (PSG) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. These studies converged on the fact that objective sleep is impacted in tinnitus patients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…O sintoma pode afetar a qualidade de vida, provocando distúrbios do sono, assim como, dificuldades sociais, de concentração, prejuízos no trabalho, percepção da fala e em alguns casos podem ocasionar desequilíbrio emocional ou problemas psiquiátricos (Almeida et al, 2009;Geocze et al, 2013;Moon et al, 2015;Sanchez et al, 2005;Teixeira et al, 2018). Ainda, segundo estudos recentes, a severidade do zumbido possui forte relação com sintomas de ansiedade e depressão, mesmo quando não provocam incômodo (Pesarico et al, 2022;Strumila et al, 2017).…”
Section: Introductionunclassified